2021
DOI: 10.5489/cuaj.6893
|View full text |Cite
|
Sign up to set email alerts
|

Longitudinal experience with Studer neobladders: Outcomes and complications

Abstract: Introduction: This study aims to assess the longer-term functional, anatomical, and metabolic outcomes of patients who underwent Studer neobladder (SNB) urinary diversion. Methods: A retrospective review of patients who underwent SNB at a single center from 1995–2017 (n=116) was performed. Demographics, comorbidities, pathological data, and longer-term functional, anatomical, and metabolic outcomes were collected from hospital records. The primary outcome was voiding function of patients at most recent f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 26 publications
0
4
0
Order By: Relevance
“…However, an 8.8% dysfunctional voiding rate (independent of physical obstruction to bladder outlet) necessitating CISC has been described by others for SN 19 . A recent series has reported a CISC rate of 22% with SN necessitated by “bladder overdistension, deteriorating renal function, or recurrent urosepsis despite timed voiding” 20 . Nerve‐sparing and younger age have been found associated with improved CISC rates 21 .…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…However, an 8.8% dysfunctional voiding rate (independent of physical obstruction to bladder outlet) necessitating CISC has been described by others for SN 19 . A recent series has reported a CISC rate of 22% with SN necessitated by “bladder overdistension, deteriorating renal function, or recurrent urosepsis despite timed voiding” 20 . Nerve‐sparing and younger age have been found associated with improved CISC rates 21 .…”
Section: Discussionmentioning
confidence: 99%
“… 19 A recent series has reported a CISC rate of 22% with SN necessitated by “bladder overdistension, deteriorating renal function, or recurrent urosepsis despite timed voiding”. 20 Nerve‐sparing and younger age have been found associated with improved CISC rates. 21 Negligible CISC rate might also have contributed to high observed post‐operative QOL summary scores.…”
Section: Discussionmentioning
confidence: 99%
“…The incidence of urolithiases in such patients seems to be increased by time. According to a longitudinal study of 72 patients with Studer pouch, urolithiasis (renal and ileal pouch) affected 28.9% of patients, primarily occurring after five years of follow-up [61]. The use of staples also has been shown to increase the risk of urolithiasis.…”
Section: Upper Tract and Pouch Stonementioning
confidence: 99%
“…The risk of metabolic acidosis is higher in neobladder compared to ileal conduit patients given the longer contact time between urine and bowel mucosa [27]. Studies have reported rates of metabolic acidosis in Studer patients treated with bicarbonate supplementation ranging from 1.1% to 4.4% [61]. However, higher rates have been presented in the literature, especially in the early postoperative period [27].…”
Section: Nutritional and Metabolic Complicationsmentioning
confidence: 99%